EXTENT BANK COLLATERAL SECURITY DEMAND ON LOANS AFFECT THE GROWTH OF SMALL SCALE ENTERPRISES IN ONITSHA, ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
Small scale enterprises are catalyst in achieving nation's economic objectives, but not without constraintsthat impede their growth. This paper ascertained the extent bank collateral Security demandon loansaffectthegrowthofsmallscaleenterprisesinOnitsha,Anambra State.Oneresearch question guided the study, whileone null hypothesis was tested at 0.05 level of significance. Descriptive survey research design was adoptedforthestudyand a population of352 owners ofsmall scale enterprisesin Onitsha,Anambra State was used forthe study. Data were collected for the study using validated structured questionnaire on a five -point ratingscale. The internal consistency of the instrument yielded an index value of 0.83, which was established withCronbach Co-efficient Alpha. The findings of the study revealed among others that bank collateral securitiesdemands on loan affected the growth of small scale enterprises at moderate, low and very low extents.However, the study showed that gender did not affect the opinion of the small scale enterprises on theextent collateral security demand affect the growth of their enterprisesin Onitsha, Anambra State. Based onthe findings of the study, it was recommended among others that entrepreneurs' in Onitsha, Anambra Stateshould embark on capacity building of their members to ensure better understanding of financialinstitutionsrequirementsforloanand thecollateraldemandsonthem.
Keywords: collateral securities, growth and small scale enterprises